Estimation of accuracy of determining video camera translational velocity according to optical flow data - Молчанов, А.А.; Кортунов, В.И. (Radiotekhnika, 2017)
Optical flow provides a tremendous opportunity for the navigation of small or micro unmanned aerial vehicles (UAVs) in the environments with a weak or absent GNSS signal. A method was proposed for determining the dynamic movement parameters based on optical flow algorithm for computing image units with weighting. The possibility of using the proposed approaches for estimating the translational velocity was given. The results of the UAV motion simulation on the underlying surface and the estimation accuracy of the determination of motion parameters using an optical sensor were shown. The experimental results confirm that the use of texture analysis increases the accuracy of the optical flow motion estimation parameters.